Odrzucenie praw Stwórcy i relacje homoseksualne w Rz 1,26-27 - Kowalski, Marcin (Verbum Vitae, 2021)
The author analyzes the Pauline pronouncement on homosexuality in Rom 1:26-27. He first places it in the context of the apostle’s arguments in Rom 1–4, outlines the structure of Rom 1:18-32, and examines the most important terms related to homosexual behavior in Rom 1:22-32. Subsequently, the author presents contemporary interpretations of Rom 1:26-27 which deconstruct or reject the Pauline critique of homosexual acts. They are divided into three basic categories: arguments from the position of modern psychology and ancient homosexual practices, arguments based on Paul’s understanding of nature, and arguments stemming from the rhetorical-literary context of Rom 1:18-32. The author critically examines these arguments, pointing to their anachronisms, limited reading of the apostle’s argumentative context, unsubstantiated overlapping of the concept of nature and cultural norm, and disregard of the universalistic character of the Pauline discourse in Rom 1:18-32.